Menelusuri Akar Toleransi Beragama dalam Sejarah Islam-Kristen di Indonesia dan Relevansinya dengan Hadis-Hadis Nabi - Syahputra, Muhammad Fauzan; Amalia, Nazwa Riza; Azis, Muhammad Abdul; Fitriani, Fitriani (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
This study investigates the historical foundations of interreligious tolerance between Muslim and Christian communities in Indonesia and examines their relevance to the Hadiths of the Prophet Muhammad. By tracing key moments of Islamic-Christian encounters—from the early spread of both religions in the archipelago to the colonial and post-independence periods—the article identifies sociocultural and theological factors that have sustained peaceful coexistence. Special attention is given to prophetic traditions (Hadiths) that advocate principles of compassion, justice, and respect for religious diversity. The findings suggest that these Hadiths not only reinforce Indonesia’s longstanding tradition of pluralism but also offer normative guidance for strengthening interfaith relations in contemporary society.